Boron carbide/graphene platelet ceramics with improved fracture toughness and electrical conductivity. Issue 12 (September 2017) - Sedlák, Richard; Kovalčíková, Alexandra; Múdra, Erika; Rutkowski, Paweł; Dubiel, Aleksandra; Girman, Vladimír; Bystrický, Roman; Dusza, Ján
Abstract: Boron carbide/graphene platelet (B4 C/GPLs) composites have been prepared with a different weight percent of GPLs as sintering additive and reinforcing phase, hot pressed at 2100 °C in argon. The influence of the GPLs addition on fracture toughness (KIC ) and electrical conductivity was investigated. Single Edge V-Notched Beam (SEVNB) method was used for fracture toughness measurements and the four-point Van der Pauw method for electrical conductivity measurements. With increasing amount of GPLs additives, the fracture toughness increased due to the activated toughening mechanisms in the form of crack deflection, crack bridging, crack branching and graphene sheet pull-out. The highest fracture toughness of 4.48 MPa.m 1/2 was achieved at 10 wt.% of GPLs addition, which was ∼50% higher than the KIC value of the reference material. The electrical conductivity increased with GPLs addition and reached the maximum value at 8 wt.% of GPLs, 1.526 × 10 3  S/m in the perpendicular and 8.72 × 10 2  S/m in the parallel direction to the hot press direction, respectively.